2020
DOI: 10.1177/1046496420956391
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Aggregation: How Voice Disparity Relates to Team Conflict, Satisfaction, and Performance

Abstract: In this manuscript, we conceptualize voice disparity based on the extent to which voice is (un)evenly communicated within a team and demonstrate its empirical utility beyond team aggregate voice. Specifically, we propose that voice disparity is negatively related to task conflict and positively related to relationship conflict, whereas the inverse holds for aggregate voice, and that conflict mediates the effects of team-level voice on team outcomes. Results of our study of 178 engineering-student teams general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 88 publications
(179 reference statements)
0
7
0
4
Order By: Relevance
“…We extend the compositional view on group diversity to a functional view of group diversity and set out to directly test the extent to which manifested diversity of viewpoint triggers intragroup conflict. Recent empirical evidence shows that when group members openly express their ideas during group meetings, groups experience more task conflict and less relationship conflict (Brykman and O’Neill, 2021). Our study extends these insights into expressed or manifested diversity and tests the impact of minority influence as a process in which one group member or a minority within a group openly expresses ideas that are different from the ideas expressed or supported by the majority (Curșeu et al , 2012b).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…We extend the compositional view on group diversity to a functional view of group diversity and set out to directly test the extent to which manifested diversity of viewpoint triggers intragroup conflict. Recent empirical evidence shows that when group members openly express their ideas during group meetings, groups experience more task conflict and less relationship conflict (Brykman and O’Neill, 2021). Our study extends these insights into expressed or manifested diversity and tests the impact of minority influence as a process in which one group member or a minority within a group openly expresses ideas that are different from the ideas expressed or supported by the majority (Curșeu et al , 2012b).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Our study extends these insights into expressed or manifested diversity and tests the impact of minority influence as a process in which one group member or a minority within a group openly expresses ideas that are different from the ideas expressed or supported by the majority (Curșeu et al , 2012b). The open expression of disagreements is a key communication process through which diversity becomes manifest in group discussions (Brykman and O’Neill, 2021); therefore, minority dissent reflects expressed or manifested diversity (Curșeu et al , 2022). In an experimental study using a hidden profile task reported in De Wit et al (2013), task conflict was induced by asking a confederate to openly express divergent opinions than the ones preferred by the other naïve participants, and this manipulation was effective.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Relationship conflict has a strong affective component (Amason, 1996), raising frustration, stress, annoyance, distrust, pushing members away from the team and enhancing negative reactions (Jehn, 1995) and emotions (Bear et al, 2014). It decreases team members' desire to remain with the team and their satisfaction toward the team (Brykman and O'Neill, 2021;Tekleab and Quigley, 2014). Individuals make negative attributions of each other in the midst of such conflict (Edmondson and Smith, 2006).…”
Section: Relationship Conflict In Military Settingsmentioning
confidence: 99%
“…Estudos recentes vêm relacionando o comportamento de voz a outros fenômenos organizacionais, como: conflito, satisfação e desempenho da equipe (Brykman & O'Neill, 2020); liderança (Hu et al, 2018;Li et al, 2018;Niu et al, 2018); percepção de suporte organizacional (Bergeron & Thompson, 2020); normas organizacionais (Kwon & Farndale, 2020). No Brasil, há um estudo voltado para a construção e validação de medidas para voz (Bastos et al, 2019a) e outro estudo acerca da voz pró-social e sua relação com o comprometimento organizacional (Bastos et al, 2018).…”
Section: Introductionunclassified